THE ROLE OF THE HOME FISH CRACKERS INDUSTRY IN INCREASING THE FAMILY ECONOMY: Case Study of Jalan Ampera, Parit Baru Village , District Selalau Sambas Regency - Sofia Safitri; Syamratun - Nurjannah (Fakultas Ekonomi dan Bisnis Islam, 2023)
The purpose of this study is to determine: (1) the role of the home industry in efforts to improve the family economy (2) Knowing the factors that are inhibiting and driving the home activity of the fish cracker industry. The method used is a descriptive method with a qualitative approach. The techniques used to collect data are observation, interview, and documentation techniques. Informants in this study were fish cracker home industry players on Jalan Ampera, Parit Baru Village, Selakau District, Sambas Regency. The results of this study can be concluded that: 1) The social economic conditions of the community who are involved in the fish cracker industry home on Jalan Ampera, Parit Baru Village, Selakau District , have improved the economy of their business actors' families. With the fulfillment of the daily living needs of the fish cracker industry home players, as well as with the improvement of the social conditions of industrial home owners ranging from better jobs, increased incomes and better children's education. 2) In the running of the home fish cracker industry there are factors that encourage it as well as inhibiting factors. There are several reasons from the community related to the reasons for carrying out home activities in the fish cracker industry, namely to maximize the potential of the surrounding nature, help the role of the husband, and as the main job. The inhibiting factors that occur in the home-carrying process out of the fish cracker industry are twofold, namely weather changes and the availability of raw materials. Keywords: Home Industry, Family Economy.